Application of Yieldable and Cuttable Pump Crib in Longwall Recovery Room - Quanzhong Gu (International Conference on Ground Control in Mining, 2004)
Stability of a pre-exnacted recovery room plays a vital role when longwall face approaches and during a longwall face move. In an attempt to extend the application of pumpable cribs into recovery room support and to limit roof bolt installation when a longwall face approaches the recovery room, yieldable and cuttable pumpable cribs (YCPC) were employed in the recovery room at the northern West Virginia mine. The YCPC consists of two layers of materials with different strengths. This allows considerable deformation from the floor and/or roof by sacrificing the soft layer while maintaining relatively high load capacity under mining¬induced front abutment loads. The thickness and stiffness of the soft layer, installation and quality control are the key factors when using the Yieldable and Cuttable Pumpable Crib to stabilize longwall recovery room- Underground observation and monitoring results show that the Yieldable and Cuttable Pumpable Crib is a viable solution to insure stability of the recovery room and can save at least two days for a longwall face move at the mine.